Constitutive Model of Solid Backfill Materials and Numerical Simulation of Overburden Movement and Deformation in Backfill Mining. (29th January 2021) - Ma, Chao; Zhang, Lianying; Li, Bing; Mao, Xianbiao
Abstract : Solid backfill mining is an efficient and environmental-friendly coal mining technology, which can effectively solve the problems of coal gangue pollution, water resource loss, and surface subsidence. Based on the mechanical behavior of backfill materials in the compaction process, volume strain was used to express the deformation modulus, and a constitutive model of backfill materials was proposed in this study. The ABAQUS UMAT was used to develop the numerical calculation subroutine of the model. Finally, the rationality of the model was verified that simulated stress-strain curves of the backfill materials during the compaction process agree well with experiments. Based on the proposed constitutive model, the influence of three factors (the initial compaction rate of the filling body, the mining height, and the mining depth) on the key strata and surface subsidence was analyzed systematically. The results show that the initial compaction rate and the height of coal seams have significant influences on surface subsidence. When the thickness of topsoil is only changed and the structural composition and lithology of overburden are not changed, the mining depth has little influence on surface subsidence, but a significant influence on surface subsidence range. The influence of mining height and mining depth on the deformation of key strata of overburden and surface subsidence is approximately linear, while the influence of the initial compaction rate is nonlinear.